Optimization of the Enzymatic Hydrolysis Assisted by Ultra-high Pressure Processing of Alaska Pollock Frame for Improving Flavour. Issue 6 (2nd July 2020) - Zhu, Wenhui; Zhu, Lunwei; Yang, Wanlin; Bu, Ying; Li, Jianrong; Li, Xuepeng
ABSTRACT: In order to improve the flavor of aquatic enzymatic hydrolysate, this study determined the effect of ultra-high pressure processing (UHP) coupled with enzymatic hydrolysis on the flavor of Alaska pollock frame (APF) hydrolysates. The optimal conditions for UHP enzymatic hydrolysis were as follows: pressure time was 60 min, pH value was 7.5, and pressure was 150 MPa. The content of soluble peptide, total-free amino acid, and delicious amino acid (DAA) content of atmospheric pressure and UHP hydrolysates were 11.37 vs 16.70 mg/mL, 5 528 vs 6 234 mg/100 g, and 2145 vs 2411 mg/100 g, respectively. The major compounds in the enzymatic hydrolysates of UHP included seven types of ketones (18.31%), 8 types of aldehydes (6.35%), 3 types of alcohols (2.61%), one type of ester (0.38%), and one type of furan (7.89%). The results of electronic tongue (e-tongue) demonstrated good agreement with gas chromatography-mass spectrometry (GC-MS) analysis. In conclusion, UHP enzymatic hydrolysis can be a potential tool to improve the flavor compounds of hydrolysates.